(untitled) (Raparin Journal of Humanities (RJH), 2023)
This study explores several converted Kurdish affixes that have come to the language from Persian and other Iranian languages. In other words, they were root morphemes in their native language. They haven’t come to the Kurdish language as roots but as affixes. That’s why, those roots have gone through borrowing and affixation. This study explores the nature and origin of those linguistic materials/items of how and where they’ve come to Kurdish language. This study explains the rules and steps of affixation. For the purpose of data analysis, ten Kurdish affixes have been used. Their outcome has been shown, through receiving all those words that have come into life because of those affixes. This study also answers this question that has been asked in Kurdish morphology about the constituent parts of those words the affixes take parts in their production. Sometimes those affixes can be words or bound morphemes. They will be analyzed based on their counterpart words meaning, or they will be analyzed based on other words in the language that their meaning is quite different from them. The results show that borrowing between languages is not restricted to words only but smaller linguistic materials/items as well, such as affixes can be borrowed from a language to another. Despite the phonetic changes that happen to a word when it comes to another language, its category and meaning can be restricted and changed but its meaning can be kept. Their outcome and ability to explain can increase with some phonetic changes.